Evaluating Climate Change Action for Sustainable Development - Uitto, Juha I.; Puri, Jyotsna; van den Berg, Rob D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a Creative Commons license. This authoritative book presents the ever progressing state of the art in evaluating climate change strategies and action. It builds upon a selection of relevant and practical papers and presentations given at the 2nd International Conference on Evaluating Climate Change and Development held in Washington DC in 2014 and includes perspectives from independent evaluations of the major international organisations supporting climate action in developing countries, such as the Global Environment Facility. The first section of the book sets the stage and provides an overview of independent evaluations, carried out by multilateral development banks and development organisations. Important topics include how policies and organisations aim to achieve impact and how this is measured, whether climate change is mainstreamed into other development programs, and whether operations are meeting the urgency of climate change challenges. The following sections focus on evaluation of climate change projects and policies as they link to development, from the perspective of international organisations, NGO$1 (Bs, multilateral and bilateral aid agencies, and academia. The authors share methodologies or approaches used to better understand problems and assess interventions, strategies and policies. They also share challenges encountered, what was done to solve these and lessons learned from evaluations. Collectively, the authors illustrate the importance of evaluation in providing evidence to guide policy change to informed decision-making.s
1. Introduction -- 2. Action on Climate Change: What Does it Mean and Where Does it Lead To? -- Part 1. Policy -- 3. Mainstreaming Impact Evidence in Climate Change and Sustainable Development -- 4. Pathway to Impact: Supporting and Evaluating Enabling Environments for Research for Development -- 5. Lessons from Taking Stock of 12 years of Swiss International Cooperation on Climate Change -- 6. An Analytical Framework for Evaluating a Diverse Climate Change Portfolio -- 7. Enhancing the Joint Crediting Mechanism MRV to Contribute to Sustainable Development -- Part 2. Climate Change Mitigation -- 8. Using Mixed Methods to Assessing Trade-offs Between Agricultural Decisions and Deforestation -- 9. Methodological Approach of the GEF IEO$1 (Bs Climate Change Mitigation Impact Evaluation: Assessing Progress in Market Change for Reduction of CO2 Emissions -- 10. Integrating Avoided Emissions in Climate Change Evaluation Policies for LDCs: The Case of Passive Solar Houses in Afghanistan -- 11.Sustainable Development, Climate Change, and Renewable Energy in Rural Central America -- 12. Unpacking the Black Box of Technology Distribution, Development Potential and Carbon Markets Benefits -- Part 3. Climate Change Adaptation.-13. What do Evaluations Tell Us About Climate Change Adaptation? Meta-Analysis with a Realist Approach -- 14. Adaptation Processes in Agriculture and Food Security: Insights from Evaluating Behavioral Changes in West Africa -- 15. Using Participatory Approaches in Measuring Resilience and Development in Isiolo County, Kenya -- 16. Evaluating Climate Change Adaptation in Practice: A Child-Centred, Community-Based Project in the Philippines -- 17. Drought Preparedness Policies and Climate Change Adaptation and Resilience Measures in Brazil: An Institutional Change Assessment -- 18. The Adaptation M&E Navigator: A Decision Support Tool for the Selection of Suitable Approaches to Monitor and Evaluate Adaptation to Climate Change.s
Keywords: Environment; Sustainability; Climatology; Environmental management; Environmental Sciences; Sustainability; Climate Sciences; Environmental Management